A Systematic Review of Clinical Outcomes in Laparoscopic versus Robotic Donor Nephrectomy - Muhammad Rizki Fadil; Fabian Gamal Sutrisno; Jeremia Yusak Lestari; Archie Fontana Iskandar (Yayasan Ilomata, 2026)
Living donor kidney transplantation remains the preferred treatment for end-stage renal disease because it provides superior long-term outcomes compared with dialysis. The increasing use of minimally invasive techniques, particularly Laparoscopic Donor Nephrectomy (LDN) and Robotic Donor Nephrectomy (RDN), has prompted comparisons of their perioperative performance and donor outcomes. This study systematically reviewed evidence comparing postoperative renal function, hospital length of stay, perioperative parameters, and postoperative complications between LDN and RDN. A systematic review following PRISMA guidelines searched PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar for comparative studies published between 2010 and 2025. Methodological quality was assessed using the Newcastle–Ottawa Scale and the JBI Critical Appraisal Checklist. Ten studies met the inclusion criteria and were synthesized qualitatively. The evidence indicates that RDN and LDN produce comparable postoperative renal function, including stable estimated glomerular filtration rate (eGFR) and serum creatinine levels. Several studies reported shorter hospital stays, lower early postoperative pain scores, and faster recovery with RDN, although robotic procedures required longer operative times during early implementation. Complication rates were generally low and similar between techniques. Overall, both LDN and RDN are feasible and safe minimally invasive approaches for living donor nephrectomy. However, variations in study design, institutional experience, and outcome reporting limit definitive conclusions regarding the superiority of either technique, highlighting the need for standardized high-quality comparative studies.